NHX-type Na+(K+)/H+ antiporters are required for TGN/EE trafficking and endosomal ion homeostasis in Arabidopsis thaliana - Dragwidge, Jonathan; Scholl, Stefan; Schumacher, Karin (Journal of cell science, 2019)
The regulation of ion and pH homeostasis of endomembrane organelles is critical for functional protein trafficking, sorting and modification in eukaryotic cells. pH homeostasis is maintained through the activity of vacuolar H+-ATPases (V-ATPases) pumping protons (H+) into the endomembrane lumen, and counter-action by cation/proton exchangers, such as the NHX family of Na+(K+)/H+ exchangers. In plants, V-ATPase activity at the trans-Golgi network/early endosome (TGN/EE) is important for secretory and endocytic trafficking; however, the role of the endosomal antiporters NHX5 and NHX6 in endomembrane trafficking is unclear. Here we show through genetic, pharmacological and live-cell imaging approaches that double knockout of NHX5 and NHX6 results in the impairment of endosome motility and protein recycling at the TGN/EE, but not in the secretion of integral membrane proteins. Furthermore, we report that nhx5 nhx6 mutants are partially insensitive to osmotic swelling of TGN/EE induced by the monovalent cation ionophore monensin, and to late endosomal swelling by the phosphatidylinositol 3/4-kinase inhibitor wortmannin, demonstrating that NHX5 and NHX6 function to regulate the luminal cation composition of endosomes.